Environmental management accounting model in the hotel industry - Masih, Ni Ketut; Wedasuari, Putu Rany; Sudana, I Made (International research journal of management, IT and social sciences, 2023)
The impact of tourism industry activities can cause various environmental problems that are detrimental to various parties. This is a social burden, which must be taken seriously. Environmental Management Accounting is a concept that helps companies contain business impacts in the form of monetary units. The application of Environmental Management Accounting helps companies deal with environmental problems by recording all production activities to be reported in the company’s environmental cost report. Although until now there is no standard that requires full environmental accounting disclosure. The research methodology uses case studies. This research aims to develop a model in the form of an accounting policy that contains the concept; emphasize relationship patterns and clarify environmental management accounting practices in the hotel industry. Data analysis was carried out using the Miles and Huberman model. The research results show that environmental management accounting is still considered necessary because it does not affect the business climate. In addition, the relationship between a company’s environmental performance presented in the company’s accountability report and its financial or economic performance is still doubtful.